2008
DOI: 10.1128/iai.01714-07
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of Cutaneous Lymph Nodes Results in a Th2 Response and Increased Susceptibility toLeishmania majorInfection in Mice

Abstract: Lymph nodes (LNs) are important sentinel organs where antigen-presenting cells interact with T cells to induce adaptive immune responses.In cutaneous infection of mice with Leishmania major, resistance depends on the induction of a T-helper-cell-1 (Th1)-mediated cellular immune response in draining, peripheral LNs. We investigated whether draining, peripheral LNs are absolutely required for resistance against L. major infection. We investigated the course of experimental leishmaniasis in wild-type (wt) mice la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Previous studies suggested that the absence of LNs leads to increased susceptibility to L. major (9, 10). We infected CD62L deficient mice on a C57BL/6 background to confirm these observations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that the absence of LNs leads to increased susceptibility to L. major (9, 10). We infected CD62L deficient mice on a C57BL/6 background to confirm these observations.…”
Section: Resultsmentioning
confidence: 99%
“…First, mice that have been engineered to express high levels of CCL21, which leads to CCR7 downregulation and therefore inhibits T cell entry into the LNs, develop a chronic disease following infection with L. major (9). Studies in mice lacking LNs highlight the importance of LNs in resistance, as these mice developed an increased susceptibility to L. major (10). We recently correlated minimal LN expansion with the susceptibility and limited immune responses seen in mice infected with L. mexicana , further suggesting the importance of this physiologic response in establishing effective immunity (8).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in a murine model of allergic airway inflammation, which is characterized by a Th2-phenotype as well, significantly more bacteria were shown to survive in the lungs of these mice after infection, possibly because of impaired host defence (56). In another context, removal of local skin-draining lymph nodes in C57BL/6 mice yielded a shift towards Th2 and consequently resulted in severe systemic infection by Leishmania major (57).…”
Section: Th2 Polarity In Allergic Diseases Correlates With Infectionsmentioning
confidence: 99%
“…The first four PPP subfamilies have been extensively investigated and are either already widely employed [82,83] or considered as promising drug targets, both in humans [79] and for development of antiparasitic drugs [4,80,81]. In a stark contrast, the PPEF/ PP7 subfamily remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%